Produksi Dan Laju Dekomposisi Serasah Hutan Kampus Institut Pertanian Bogor, Kabupaten Bogor, Indonesia - Firman Ali Rahman; Taufik Arianto; Sulistijorini; Aisha Zea Almahyra; Arsya Zafran Alvarendra; Mai Rizali (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2023)
Forests are important habitats that support an ecosystem consisting of various types of plants that have production potential and litter decomposition rates. This research aims to find out how to calculate the production and decomposition rate of litter in homogeneous forest and heterogeneous forest terrestrial ecosystems. The research was carried out in homogeneous and heterogeneous forest areas in the IPB University campus area, Bogor Regency, West Java Province. The sampling process seemed to be carried out using 1x1 m nylon mesh litter trap method for 5 weeks. The results of the research show that the composition of the species that grow in heterogeneous forest areas is Kisabun (Filicium decipien), Sawo kecik (Manilkara kauki), Bisbul (Diospyros blancoy), Water guava (Eugenia aduea), Matoa (Pometia pinnata), Pinus (Cupressus lusitanica), and Meranti (Shorea sp), while in the homogeneous forest ecosystem is the rubber tree (Hevea brasiliensis). The amount of waste collected in heterogeneous forest ecosystems is greater than in homogeneous forest ecosystems (Rubber forests), namely 98 grams and 5.2 grams respectively with results in heterogeneous forest ecosystems of 7.2 grams dry weight from 10 grams wet weight, whereas in homogeneous forest ecosystem (rubber forest 0.8 grams dry weight from 2 grams wet weight). The decomposition rate of litter in heterogeneous ecosystems is 0.21 grams/year, while in rubber forest ecosystems it is 0.17 grams/year.